2021
DOI: 10.5089/9781513575926.001
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Employment in the COVID-19 Recession: Evidence on “She-cessions”

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 9 publications
2
24
0
1
Order By: Relevance
“…In recent years, “invisible” poverty has been reported to have become more severe among the younger generation, especially among single-mother households in Japan [ 32 - 34 ]. Furthermore, compared to the economic downturn caused by the Lehman Brothers shock, which had a large impact on males in the manufacturing industry, the economic downturn caused by the COVID-19 pandemic has had a large impact on females and is sometimes referred to as she-cession [ 8 , 35 ]. A decrease of 700,000 female workers against 390,000 male workers has occurred in Japan since the COVID-19 pandemic began.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, “invisible” poverty has been reported to have become more severe among the younger generation, especially among single-mother households in Japan [ 32 - 34 ]. Furthermore, compared to the economic downturn caused by the Lehman Brothers shock, which had a large impact on males in the manufacturing industry, the economic downturn caused by the COVID-19 pandemic has had a large impact on females and is sometimes referred to as she-cession [ 8 , 35 ]. A decrease of 700,000 female workers against 390,000 male workers has occurred in Japan since the COVID-19 pandemic began.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that employment status and economic factors are associated with suicide [ 6 , 7 ], which may have increased because of the impact of the pandemic on the labor market. Unlike the Lehman Brothers shock, which had a major impact on the manufacturing industry and the male labor market, the influence of COVID-19 has had a strong adverse impact on the female labor market and has been referred to as “she-cessions” [ 8 ]. Furthermore, women in Japan are likely to be at higher risk than men because they have often lagged in terms of educational standards and working conditions and have been severely affected by the pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reductions in female participation are explained by the departure of women from the labor market to dedicate themselves to the care of their children. In an analysis of the labor markets of 20 developed and developing countries, Bluedorn et al (2021) found that women had experienced greater reductions in the participation rate than men, and that these differences explained the differentiated impacts by gender of the Covid pandemic. Data corresponding to April-June 2020, in relation to the same quarter of 2019, published by ECLAC (2021c) for eight Latin American countries, show that the pandemic has led to more pronounced job losses for the young population between 15 and 24 years than for the population over 24 years of age.…”
Section: Repercussions Of the Covid Pandemic On Employmentmentioning
confidence: 99%
“…The authors concluded by emphasizing the importance of offering cash transfers and food to the low-income population to ensure that quarantines were effective in stopping the spread of the pandemic. Bluedorn et al (2021) have pointed out that there is no basis for forecasting which sectors will be the fastest to ijef.ccsenet.org International Journal of Economics and Finance Vol. 13, No.10;2021…”
mentioning
confidence: 99%
“…The devastating economic impact of the COVID-19 pandemic has been shown to differ widely among demographic and socioeconomic groups (Chetty et al, 2020). Although the issue of young individuals being one of the categories hit the most has been vocally raised in Europe (Eurofound, 2020) and extensively acknowledged in the literature (Lee et al, 2021;Alon et al, 2021;Bluedorn et al, 2021;Adams-Prassl et al, 2020;Blustein et al, 2020), surprisingly there are few specific quantitative studies on the topic. In this paper, we investigate how the COVID-19 pandemic has affected the careers of young individuals aged 15-34 in Italy.…”
Section: Introductionmentioning
confidence: 99%